Leonardo da Vinci volume 1. - Müntz, Eugène, 1845-1902 (Temporis collection., 2012)
"Studying nature with passion, and all the independence proper to his character, he could not fail to combine precision with liberty, and truth with beauty. It is in this final emancipation, this perfect mastery of modelling, of illumination, and of expression, this breadth and freedom, that the master's raison d'être and glory consist. Others may have struck out new paths also; but none travelled further or mounted higher than he." (Eugène Müntz).